2020
DOI: 10.1111/jon.12749
|View full text |Cite
|
Sign up to set email alerts
|

Microembolic Signals Detected by Transcranial Doppler Predict Future Stroke and Poor Outcomes

Abstract: BACKGROUND AND PURPOSE: Although transcranial Doppler detects microembolic signals (MES) in numerous settings, the practical significance of such findings remains unclear. METHODS: Clinical information from ischemic stroke or transient ischemic attack patients (n = 248) who underwent embolic monitoring from January 2015 to December 2018 was obtained. RESULTS: MES were found in 15% of studies and ischemic recurrence was seen in 11% of patients (over 7 ± 6 days). Patients with MES had more lacunes than those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…High SUV MAX and R1 MAX values in the TEE negative subjects were also associated with high risk features such as the presence of a hypercoagulable state (Factor V Leiden) or history of cerebral thromboembolism. While very preliminary, these observations in the TEE negative cohort raise the possibility that small microthrombi, undetectable by TEE, may be present in the LAA during atrial fibrillation (44)(45)(46). Studies using transorbital Doppler in TEE negative subjects have documented multiple embolic signals to the brain, supporting the presence of subclinical microthrombi in atrial fibrillation.…”
Section: Discussionmentioning
confidence: 70%
“…High SUV MAX and R1 MAX values in the TEE negative subjects were also associated with high risk features such as the presence of a hypercoagulable state (Factor V Leiden) or history of cerebral thromboembolism. While very preliminary, these observations in the TEE negative cohort raise the possibility that small microthrombi, undetectable by TEE, may be present in the LAA during atrial fibrillation (44)(45)(46). Studies using transorbital Doppler in TEE negative subjects have documented multiple embolic signals to the brain, supporting the presence of subclinical microthrombi in atrial fibrillation.…”
Section: Discussionmentioning
confidence: 70%
“…In addition to hemodynamic compromise, there are increasing evidence that supports the causality between thromboembolic mechanisms and MMD relevant infarctions [ 15 , 26 28 ]. Microembolic singles are frequently detected by transcranial Doppler before and after surgery in MMD patients, and their association with previous ischemic events and predictive value of future cerebral events has been verified in several TOAST subtypes [ 26 , 29 31 ]. Unless back to normal, the extensive moyamoya network may constantly serve as a fountain of emboli thereby contribute to subsequent ACEs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that patients with MES are prone to re-occurrence of cerebral ischemia (HR: 4.90, 95% CI 2.16-11.09, P < 0.001) and a more severe functional impairment after thrombosis (OR: 3.31, 95% CI 1.22-8.99, P = 0.019) (Das et al, 2020). Sheriff et al (2020) utilized TCD to monitor microembolic signals in the patients after successful thrombectomy and the patients with anterior circulation occlusion. In brief, MES signals were detected in 43 of 111 patients, with a median rate of 4 times/h; on 24-h computed tomography, similar infarct volume [adjusted β = 11.2 (95% CI: −46.6 to 22.9), P = 0.51] was observed in patients with or without MES; besides, MES also predicted new embolic events [Cox hazard ratio 6.78 (CI 95% 1.63-27.8), P = 0.01].…”
Section: Monitoring Of Microembolimentioning
confidence: 99%
“…Specifically, the backscatter of ultrasound from gaseous emboli is higher than that from the solid emboli and red blood cells ( Wojczal et al, 2002 ). Studies have demonstrated that patients with MES are prone to re-occurrence of cerebral ischemia (HR: 4.90, 95% CI 2.16–11.09, P < 0.001) and a more severe functional impairment after thrombosis (OR: 3.31, 95% CI 1.22–8.99, P = 0.019) ( Das et al, 2020 ). Sheriff et al (2020) utilized TCD to monitor microembolic signals in the patients after successful thrombectomy and the patients with anterior circulation occlusion.…”
Section: Guidance On Thrombolysismentioning
confidence: 99%